Dietary and complementary oral supplements for the management of chronic diseases in children: a systematic review - Inchingolo, Alessio Danilo; Marinelli, Grazia; Limongelli, Luisa; Inchingolo, Francesco; Favia, Gianfranco; Ferrante, Laura; Di Noia, Angela; Maspero, Cinzia; Palermo, Andrea; Inchingolo, Angelo Michele; Dipalma, Gianna (Frontiers in Pediatrics, 2026)
AimChronic diseases in childhood and adolescence represent a growing global challenge, with families often seeking complementary strategies beyond pharmacological treatment. This systematic review aimed to evaluate the efficacy and safety of dietary and oral supplements in pediatric chronic diseases.Materials and methodsThe review was conducted in accordance with PRISMA guidelines. A systematic search of PubMed, Scopus, Web of Science, and Cochrane Library was performed (2005–2025). Eligible studies enrolled children and adolescents (<18 years) with chronic diseases and assessed oral dietary supplements against placebo, standard care, or no intervention. Thirteen studies were included.ResultsThe studies investigated autism spectrum disorder (ASD), functional gastrointestinal disorders, cystic fibrosis (CF), type 1 diabetes (T1D), bronchopulmonary dysplasia (BPD) and juvenile idiopathic arthritis. Interventions included probiotics, omega-3/6 fatty acids, vitamins, minerals, glutathione, Kre-Celazine® and Dimercaptosuccinic Acid (DMSA). Most supplements demonstrated measurable bioactivity, such as modulation of the gut microbiota, changes in inflammatory markers, or improvements in functional indices, but clinical benefits were often inconsistent or limited to subgroups. Safety was generally favorable for probiotics, polyunsaturated fatty acids, magnesium, zinc, and vitamin A, whereas DMSA chelation raised significant safety concerns.ConclusionsDietary and oral supplements show promise as supportive interventions in pediatric chronic diseases but cannot yet be recommended for systematic clinical use. Larger multicenter trials with longer follow-up, standardized endpoints, and predictive biomarkers are needed to identify responder subgroups and establish evidence-based recommendations.